2021
DOI: 10.1111/plb.13219
|View full text |Cite
|
Sign up to set email alerts
|

Optimal NH4+/NO3 ratios enhance the shade tolerance of soybean seedlings under low light conditions

Abstract: In the maize–soybean intercropping system, shade is the major chronic restraint that affects normal growth of soybean. Different spatial patterns of this system affect the microclimate of soybean through shading from maize plants. However, the negative impacts of shading stress can be mitigated by providing optimal ratios of different fertilizers. Therefore, to test this hypothesis, soybean plants were grown under different light conditions (normal light or shade) to evaluate the response to varying NH4+/NO3− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…In another study on cabbage, it is reported that NH4 + :NO3ratio has no impact on leaf count (Assimakopoulou et al, 2019). Raza et al (2021) demonstrate that only NH4 + or NO3applied to soybeans under normal or low light availability, leaf fresh and dry weights decreased. However, they also reported that if both N forms are applied together, these levels increase.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…In another study on cabbage, it is reported that NH4 + :NO3ratio has no impact on leaf count (Assimakopoulou et al, 2019). Raza et al (2021) demonstrate that only NH4 + or NO3applied to soybeans under normal or low light availability, leaf fresh and dry weights decreased. However, they also reported that if both N forms are applied together, these levels increase.…”
Section: Discussionmentioning
confidence: 80%
“…The NH4 + :NO3ratio can be used as a strategy to eliminate abiotic stresses such as low light availability, salinity, drought, and heat. Numerous studies have suggested that growing plants with only NH4 + or NO3with various NH4 + :NO3ratios can affect tolerance of plants low light availability (Raza et al, 2021), water stress (Shang and Shen, 2018) or salinity (Meng et al, 2016;Ashraf et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen (N) is a nutrient that plays a key role in plant growth and development, and ammonia-nitrogen (NH 4 + -N) and nitrate-nitrogen (NO 3 − -N) are the two main N forms absorbed and utilized by plants [1]. NH 4 + enters the plant and combines with organic acids to form amino acids and amides [2]; NO 3 − is absorbed into plants and cannot be used directly by plants: part of it is reduced to NH 4 + [3], and part is stored in vacuoles [4]. Different plants have different preferences for the uptake of NH 4 + and NO 3 − .…”
Section: Introductionmentioning
confidence: 99%
“…3) [141][142][143][144][145]. Among the inducers of oxidative stress, light (intensity or spectrum) is one of the most important ones [3][4][5][6][7]. It is widely reported that exposure to high light intensities resulted in altered redox status of plants which may lead to great metabolic modifications as observed in wheat [8][9][10][11][12][13].…”
Section: Effect Of Environment On the Redox Systemmentioning
confidence: 99%
“…Among the inducers of oxidative stress, changes in light intensity or spectrum are very important, the alteration of which may result in pronounced modifications of wheat metabolism [3][4][5][6][7]. It is widely reported, that high light-induced oxidative stress modified the redox status of plants [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%